Induced abortion in Toplica district as a public health problem - Arsić, Dragutin; Milenković, Aleksandra (PONS - medicinski časopis, 2014)
ABSTRACT Objective. The aim of study was to determine frequency of induced abortion during a five-year period in Toplica count, basic socio-demographic determinants of a woman and analyze methods of contraception. Methods. Data abortion incidence has been collected from documents of General Hospital Prokuplje, 2009-2013. year and other parameters for 2012-2013. Level of knowledge about protection during sex was collected by surveying a random sample of 50 women aged 20-50 years. Results. Fluctuations in number of induced abortions (174, 191, 154, 163, 148) were not significant (p=0.135). The highest number of induced abortions was at age 20-29 years. There was no difference within subpopulations of women by age between two studied periods (p=0.871). Married women had more abortion as well as women at city than in countryside. Women with 2 previous births were prevailing (46%) as well as women in which the induced abortions were the first one (28.6%). Abortions were performed at 6-10 weeks, usually in the 8th week of gestation, in both years (p=0.500). Protection during sexual intercourse used 36% of women, did not use 48% ones and sometimes used 16% women. Of respondents who regularly or occasionally use contraception 20% of them used oral contraceptives, 16% used a condom, while a smaller number are used combination or other traditional methods. Conclusion. Incidence of induced abortions in study population of women is high, there were no significant fluctuations in incidence as well as in women’s socio-demographic factors, and use of modern contraceptive methods is unsatisfactory. Key word: abortion, induced; contraception; public health.